2020
DOI: 10.21307/ijssis-2020-024
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hybrid PAPR Reduction Techniques on FBMC for 5G Applications

Abstract: The filter bank multicarrier (FBMC) system suffers from the non-linear effects that arise due to a high peak-to-average power ratio (PAPR). Diverse precoding techniques are utilized to enhance the efficiency and robustness of FBMC. A high PAPR in the FBMC system can be overcome by a unique combination of precoding and conventional PAPR reduction techniques proposed in this paper. Different precoding schemes, discrete sine transform (DST) and discrete cosine transform (DCT), are combined with different PAPR red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Thus, high-power amplifiers must be operated at the transmitter. The FBMC system uses an OFDM-based PAPR reduction approach, such as absolute exponential companding, logarithmic rooting, tangent rooting, the A-law, and rooting [100], [101]. The objective outlined in [76], [100], [101] is to reduce the PAPR issue.…”
Section: ) Orthogonal Multiple Access (Oma)mentioning
confidence: 99%
“…Thus, high-power amplifiers must be operated at the transmitter. The FBMC system uses an OFDM-based PAPR reduction approach, such as absolute exponential companding, logarithmic rooting, tangent rooting, the A-law, and rooting [100], [101]. The objective outlined in [76], [100], [101] is to reduce the PAPR issue.…”
Section: ) Orthogonal Multiple Access (Oma)mentioning
confidence: 99%
“…The model consequences confirm that the enactment of the projected process is superior to the prevailing systems. In [10], the PAPR of the FBMC wave is lowered by applying DCT and DST algorithms. The outcomes of the simulation show that the simulation shows that the proposed method effectively obtains a gain of 5 to 10 dB.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [ 31 ] introduced DST-A without any comparison with the previous precoding-companding techniques. The authors in [ 32 ] showed that DST- is better than DST-A and DCT-A from PAPR reduction and BER points of view. Recently, DCT- has been compared with DCT- -clipping in [ 33 ], only from the PAPR reduction point of view.…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of the discussed works are summarized as follows: The authors in [ 22 , 24 , 27 , 28 , 30 , 32 , 33 , 34 , 36 , 37 ] hybridized -law with different precoding matrices due to its high PAPR reduction gain. However, BER and OOB radiation are more important metrics than PAPR reduction gain when working with PAPR reduction techniques that cause BER degradation, such as companding techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation